KECERDASAN BUATAN PADA SISTEM KUNCI MOTOR MENGGUNAKAN VOICE RECOGNITION BERBASIS RASPBERRY PI - Rizkia, Risang (Jurnal Kreativitas Mahasiswa Informatika, 2022)
Abstract This automatic motor lock system represents an alternative to modern control systems that use voice detection and commands or Voice Recognition to turn the motor on and off with a system response of 3 seconds. This motor is driven by a dc motor based on the results of voice command processing by the Raspberry Pi which has an efficient sound reception distance of 10-20 centimeters from the received sound source. Keywords : Voice Recognition, Raspberry Pi, Auto Lock. Abstract This automatic motor lock system represents an alternative to modern control systems that use voice detection and commands or Voice Recognition to turn the motor on and off with a system response of 3 seconds. This motor is driven by a dc motor based on the results of voice command processing by the Raspberry Pi which has an efficient sound reception distance of 10-20 centimeters from the received sound source. Keywords : Voice Recognition, Raspberry Pi, Auto Lock.